Review of the Adequacy of the Fund's Precautionary Balances. (Policy Papers; Policy Paper ;, 2021)
On October 30, 2020, the IMF's Executive Board reviewed the adequacy of the Fund's precautionary balances. Precautionary balances, comprising the Fund's general and special reserves and the Special Contingent Account (SCA-1), are one element of the IMF's multi-layered framework for managing financial risks. These balances provide a buffer to protect the Fund against potential losses, resulting from credit, income, and other financial risks. This review of the adequacy of the Fund's precautionary balances took place on the standard two-year cycle, although it was delayed by a few months to allow for an assessment of the impact of the COVID-19 pandemic on Fund financial risks. In conducting the review, the Executive Board applied the rules-based framework agreed in 2010.